Proton Exchange Membrane Fuel Cells: Effects of Gas Diffusion Layer Porosity Differences - Kabouchi Kaoutar; Ettouhami Mohamed Karim (E3S Web of Conferences)
Fuel cells are a key technology for clean energy production due to their low environmental impact and their high efficiency, yet optimizing their performance remains challenging, particularly regarding the gas diffusion layer (GDL). The GDL is critical for distributing reactants and removing products within the cell. This study employs a 3D model, built in COMSOL Multiphysics, to simulate and assess fuel cell performance at different GDL porosity levels. The porosity varied from 0.2 to 0.8 in increments of 0.1, while all other material properties were kept constant. The results show that increasing porosity improves performance, with a strong correlation between simulation and experimental data. Polarization curves highlight the effect of GDL porosity on cell efficiency. This model offers valuable insights for optimizing fuel cell designs by adjusting GDL properties, contributing to the development of more efficient, cost-effective, and durable fuel cells for clean energy applications.